2011
DOI: 10.1117/1.3599958
|View full text |Cite
|
Sign up to set email alerts
|

Detection of rheumatoid arthritis by evaluation of normalized variances of fluorescence time correlation functions

Abstract: Abstract. Fluorescence imaging using the dye indocyanine green as a contrast agent was investigated in a prospective clinical study for the detection of rheumatoid arthritis. Normalized variances of correlated time series of fluorescence intensities describing the bolus kinetics of the contrast agent in certain regions of interest were analyzed to differentiate healthy from inflamed finger joints. These values are determined using a robust, parameter-free algorithm. We found that the normalized variance of cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(36 citation statements)
references
References 15 publications
0
35
0
1
Order By: Relevance
“…So far, different methods for interpreting the FOI results have been deployed [8,19,28]. Werner et al [8] used a semiquantitative score, where the signal enhancement has been graded in percentages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, different methods for interpreting the FOI results have been deployed [8,19,28]. Werner et al [8] used a semiquantitative score, where the signal enhancement has been graded in percentages.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, another study by Meier et al [19] reported that FOI had a sensitivity of 39.6% and a specificity of 85.2%, compared with MRI demonstrating conflicting results regarding the reliability of this new method. In 2011 Dziekan et al [28] proposed a quantitative analysis of FOI using normalized variances of fluorescence time correlation functions. In their pivotal pilot study, the joints of healthy volunteers and patients with RA were compared, but no other imaging techniques besides FOI were employed.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that NIRF imaging using these nonspecific dyes has the potential for detection of inflammatory joints. 24,26 In the current study we investigated the enhancement induced by the nonspecific NIRF dye TSC in ankle joints of rats with CIA. TSC is a well-tolerated cyanine dye of similar chemical nature as ICG; however, its in vivo properties (plasma binding, circulation time) are different from those of ICG.…”
Section: Discussionmentioning
confidence: 99%
“…22 A promising nonspecific dye is tetrasulfocyanine (TSC), a modified cyanine dye which was already successfully used for in vivo imaging of subcutaneously growing tumors in animals. 23 Clinical trials are under way to investigate different nonspecific NIRF dyes for the visualization of arthritis [24][25][26] and superficial tumors, e.g., in optical mammography. [27][28][29] TSC was selected for our experimental investigation because this dye exhibits increased hydrophilicity and less plasma protein binding, and therefore may possess improved imaging properties compared with ICG.…”
mentioning
confidence: 99%
“…These data are in accordance with our previous findings in humans and experimental arthritis. 11,14,21,22 …”
Section: Arthritis Severity and Nirf Imaging Before Therapymentioning
confidence: 99%